Investigation of a hydrogen generator with the heat management module utilizing liquid‐gas organic phase change material. (27th February 2021) - Kwak, Yeonsu; Shin, Hyunah; Moon, Seongeun; Lee, Kwanhee; Kirk, Jaewon; Park, Yongha; Jeong, Hyangsoo; Sohn, Hyuntae; Han, Jong Hee; Nam, Suk Woo; Yoon, Chang Won; Kim, Yongmin; et al.
Summary: Hydrogen carriers have been actively explored as a viable option for safe and economical hydrogen storage and transportation. However, the highly endothermic nature of dehydrogenation reactions results in a considerable temperature nonuniformity due to severe heat transfer limitations. To address this issue, a bench‐scale catalytic reactor for hydrogen production is developed from methanol steam reforming (MSR) using a liquid‐gas organic phase change material (PCM) working at a medium temperature range (200°C‐300°C) and near‐ambient pressure conditions. First, a comparative study was conducted to quantify the temperature homogeneities with or without adopting PCM; the former showed a higher temperature uniformity, leading to an improved hydrogen production rate and system efficiency. Additionally, a rapid start‐up and uniform temperature profile of the catalytic bed at a steady state by the thermal management of the PCM were manifested. The liquid‐gas organic PCM was stable during MSR at 250°C, despite minor oxidation. For the feasibility study on a bench scale, 0.6 kWe ‐level hydrogen generation (equivalent to 5.83 kWe /Lreactor ) using the PCM‐based reactor was demonstrated. This work can provide insights into the scale‐up and thermal management of various catalytic dehydrogenation reactors encompassing considerable heat absorption or release. Abstract : The article investigates i) the adoption of liquid‐gas organic phase change material (PCM) as heat transfer medium working in the medium‐temperature range (200~300 °C) for endothermic dehydrogenation reaction, ii) the development of a compact bench‐scale hydrogen generator with PCM‐based heat management module and its experimental demonstration, and iii) the productivity, efficiency, and heat transfer comparative analysis of the hydrogen generator with or without the as‐developed heat management system.